2008
DOI: 10.1073/pnas.0710643105
|View full text |Cite|
|
Sign up to set email alerts
|

Enzyme structure and dynamics affect hydrogen tunneling: The impact of a remote side chain (I553) in soybean lipoxygenase-1

Abstract: This study examines the impact of a series of mutations at position 553 on the kinetic and structural properties of soybean lipoxygenase-1 (SLO-1). The previously uncharacterized mutants reported herein are I553L, I553V, and I553G. High-resolution x-ray studies of these mutants, together with the earlier studied I553A, show almost no structural change in relation to the WT-enzyme. By contrast, a progression in kinetic behavior occurs in which the decrease in the size of the side chain at position 553 leads to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

23
294
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 153 publications
(318 citation statements)
references
References 36 publications
23
294
1
Order By: Relevance
“…Mounting data for enzymes that transfer hydrogen by a tunneling mechanism have led to a model for enzyme catalysis that implicates at least two classes of protein motion (15,16,(25)(26)(27)(28)(29)(30). Tunneling has been modeled with an expanded Marcus-like equation that assigns the thermal reaction barrier to the environmental reorganization terms that produce transient degeneracy between reactant and product wells and lead to sampling of a range of donor-acceptor distances (31)(32)(33).…”
Section: Discussionmentioning
confidence: 99%
“…Mounting data for enzymes that transfer hydrogen by a tunneling mechanism have led to a model for enzyme catalysis that implicates at least two classes of protein motion (15,16,(25)(26)(27)(28)(29)(30). Tunneling has been modeled with an expanded Marcus-like equation that assigns the thermal reaction barrier to the environmental reorganization terms that produce transient degeneracy between reactant and product wells and lead to sampling of a range of donor-acceptor distances (31)(32)(33).…”
Section: Discussionmentioning
confidence: 99%
“…To assess tunneling contributions to catalysis, it is rare that a reaction in water can be compared with the same reaction catalyzed by an enzyme in sufficient detail (2,12). In the present study, we present overwhelming evidence demonstrating quantitatively differential NQE that contributes to catalysis in NAO: We found that the overall NQE has a greater contribution to lowering the classical barrier in the enzyme, and there is a larger difference in quantum effects between proton and deuteron transfer for the enzymatic reaction than the uncatalyzed one.…”
Section: Discussionmentioning
confidence: 99%
“…Although tantalizing, the relatively small difference in the observed KIEs is not sufficient to conclude that there is a greater tunneling contribution in the enzymatic process than that of the uncatalyzed reaction in water. A number of experimental and theoretical studies suggested that the extent of tunneling was the same in several enzymes as in model reactions in solution (2,9,10), whereas other experiments showing differential tunneling behaviors may be attributed to different reaction mechanisms (2,(11)(12)(13). Nuclear tunneling cannot be measured directly, and the best experimental diagnostic of tunneling is through measurement of kinetic isotope effects (14).…”
mentioning
confidence: 99%
“…The nature and magnitude of these forces remains an active area of research. [10][11][12][13][14][15] Enzymes have evolved to create elaborate active sites containing precise arrangements of hydrogen-bonding networks, electrostatic interactions, and functional group availability specifically aimed at increasing the reactivity of bound substrates. While the development of synthetic host-guest systems has not reached the level of enzyme specificity, the characteristics of each synthetic assembly, such as the size, shape, charge, and functional group availability, greatly influence the guest-binding characteristics and have led to remarkable and often unexpected reactivity.…”
Section: Introductionmentioning
confidence: 99%